Supporting and enabling health research in a local authority (SERLA): an exploratory study - Ciara E. McGee; Megan Barlow-Pay; Ivaylo Vassilev; Janis Baird; Lee-Ann Fenge; Debbie Chase; Julie Parkes (BMC, 2022)
Abstract Background The use of research evidence to underpin public health practice and policy decisions in local government is strongly promoted but its implementation has not been straightforward. This study aimed to explore the factors, relationships and processes that contribute towards accessing, using, and generating research evidence that is relevant to local authority public health and social care and shapes its practice. Methods Semi-structured individual interviews with elected councillors, officers directly involved with public health and social care and with community members from one urban unitary authority in South England were conducted. Interviews were audio recorded, transcribed verbatim and thematically analysed. Results Fourteen participants took part in the semi-structured interviews. Local knowledge and evidence are prioritised, and anecdotal evidence is valued. The Director of Public Health was the principal source of information and support. Academics were rarely mentioned as information sources, and their involvement was ad hoc. The use of research evidence varied between individuals and departments, with wider engagement among public health specialists. Key barriers to the use of research evidence included access (not reported among public health professionals), research timeliness, local applicability, competence in finding and interpreting evidence and the role of research evidence within a political context. Public health and adult social care teams are not currently research active or research ready. Major barriers exist due to financial constraints and the socio-political context of local authorities. COVID-19 disrupted siloed ways of working, strengthening and opening potential collaborations within the local authority. This changed perspectives about the value of research but is likely time-limited unless underpinned by sustainable funding. Conclusion Creating strategic level roles within local government to work with the Director of Public Health to champion the research agenda and embedding researchers within and across teams would build capacity for local authorities to sustainably co-create, undertake, and use evidence to better inform future actions.